Anti‐Inflammatory and Antioxidative Properties of Isoflavones Provide Renal Protective Effects Distinct from Those of Dietary Soy Proteins against Diabetic Nephropathy. Issue 10 (27th April 2020) - Jheng, Huei‐Fen; Hayashi, Kanako; Matsumura, Yasuki; Kawada, Teruo; Seno, Shigeto; Matsuda, Hideo; Inoue, Kazuo; Nomura, Wataru; Takahashi, Haruya; Goto, Tsuyoshi
Abstract : Scope: Dietary soy reportedly protects from diabetic nephropathy (DN), but its active components and mechanism of action remain unknown. Methods and results: In this study, KKAy mice are fed three types of diet: Dietary soy isoflavones with soy protein (Soy‐IP) diet, reduced isoflavones soy protein (RisoP), and oral administration of isoflavones aglycones (IsoAgc). Albuminuria and glycosuria are decreased only in the soy‐IP group. The risoP group show reduced expansion of mesangial matrix and renal fibrosis, the IsoAgc group show renal anti‐fibrotic and anti‐inflammatory effects; however, these renal pathological changes are repressed in the soy‐IP group, suggesting the distinct protective roles of soy protein or isoflavones in DN. The isoflavone genistein has a better inhibitory effect on the inflammatory response and cellular interactions in both mouse tubular cells and macrophages when exposed to high glucose and albumin (HGA). Genistein also represses HGA‐induced activator protein 1 activation and reactive oxidases stress generation, accompanied by reduced NADPH oxidase (NOX) gene expression. Finally, diabetic mice show a decrease in lipid peroxidation levels in both plasma and urine, along with lower NOXs gene expression. Conclusion: The data elucidate the detailed mechanism by which isoflavones inhibit renal inflammation and provide a potential practical adjunct therapy to restrict DN progression. Abstract : Soy isoflavone and protein have their own merits on diabetic nephropathy protection. Soy protein reduces glomerulus sclerosis, while soy isoflavone has better anti‐inflammatory effects. Furthermore, the isoflavones, especially genistein, have a better inhibitory effect on the inflammatory response which may operate through a repression of the ROS/ERK/AP1 pathway.